TOPONYMS ARE AMBASSADORS OF HISTORICAL PERIODS (World Bulletin of Social Sciences, 2024)
The vast majority of toponyms arise in connection with the topography and geographical features of the area. As a result, over time, a number of sounds, undergoing changes that originally meant their lexical meaning, move to surrounding places, historical monuments and settlements. Such names include Dugob, Orgashkan (Orgoshgon), Darband, which contain many historical events and riddles. Their comprehensive analysis allows us to establish the historical names of toponyms accurately.
Keywords: Land relief; Dugob; Orgashkan; Darband